OPTIMASI VARIASI KONSENTRASI TWEEN 80 PADA FORMULASI NANOEMULSI KOMBINASI EKSTRAK DAUN PEGAGAN DAN DAUN KELOR - devanus lahardo; yafet Pradikatama Prihantono (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Abstract. This study aims to optimize the nanoemulsion formulation of combined extracts of Centella asiatica and Moringa oleifera leaves using varying concentrations of Tween 80 as a surfactant. Three formulas were prepared with 8%, 10%, and 12% Tween 80. Physical evaluations included particle size, pH, and viscosity. Results showed that increasing Tween 80 concentration increased particle size and viscosity, while pH remained relatively stable. The 8% Tween 80 formula yielded the most optimal result with the smallest particle size and suitable viscosity for topical application. One-way ANOVA revealed significant differences in particle size and viscosity, but not in pH. These findings indicate that Tween 80 concentration affects the physical stability of the nanoemulsion Key words: kelor leaves, pegagan leaves, nanoemulsion, tween 80